Reception history and the trauma of real history - Korsyn, Kevin Ernest (Muzikološki zbornik, 2009)
Haydn's incorporation of a pantomime into the finale of the 'Farewell' Symphony constitutes as radical a violation of generic expectations as Beethoven's introduction of a chorus in the Ninth symphony, yet until now no one has analyzed this pantomime or decoded its meanings. The reception history of this piece suggests a paradoxical mixture of heightened historical recollection with a sort of willed amnesia.
Keywords: Freud, Sigmund, 1856-1939; glasba; Haydn, Joseph, 1732-1809; history; Lacan, Jacques, 1901-1981; memory; music; pantomime; politics; politika; ponavljanje; recepcija; spomin; travme; zgodovina; Žižek, Slavoj, 1949-